Strategi Guru Bimbingan Dan Konseling (BK) Dalam Membantu Mengatasi Kesulitan Belajar Siswa MTs Daruth Tholibiin Nganjuk - Moh. Nasrulloh; Muslimin (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2019)
This study wants to see the effect of BK on overcoming student learning difficulties at MTs Daruth Tholibiin Nganjuk. Learning difficulties are naturally experienced by all students, but not all schools or teachers are able to help students overcome these problems. Almost all schools also have counselling guidance teachers. However, in practice, BK teachers also have differences in dealing with student problems. Because of different cultures, habits and situations. In this study using a qualitative approach, because the qualitative approach has characteristics including natural setting and researchers as key instruments, descriptive research and inductive data analysis. In collecting data using the method of observation, interviews and documentation. While the data analysis uses descriptive qualitative techniques. From this study, it can be concluded how the teacher guidance and counselling strategy in overcoming the learning difficulties of MTs Daruth Tholibiin students. Guidance and counselling (BK) teacher strategies in helping students overcome learning difficulties are carried out through classical learning orientation and information during one hour of learning, holding counselling in a special room for guidance and counselling services, conducting case conferences and holding follow-up in collaboration with teachers in the field of study and parents of students.